Endobronchial Metastasis of Malignant Melanoma Presenting with Dyspnea: Case Report and Literature Review - ÇELİKEL, ÇİĞDEM; KARAKURT, SAİT (ORTADOGU AD PRES & PUBL CO, 2011)
Malignant melanoma occurs due to malignant transformation of melanocytes. It has a high mortality rate. Pulmonary metastases are rarely seen and occur via pulmonary arterial embolism. Other sites for metastases are regional lymph nodes, bones and central nervous system. Endobronchial metastatic solid tumors can simulate bronchogenic carcinoma and can present with cough, dyspnea, hemoptysis and wheezing. Malignant melanoma with endobronchial seeding is rare. Histopathological features of the bronchoscopic biopsy and brushing usually reveal the definitive diagnosis in the cases of endobronchial metastasis. We report a case of malignant melonoma with endobronchial metastases diagnosed via bronchoscopy.
Keywords: Melanoma; neoplasm metastasis; bronchoscopy; CANCER STATISTICS